Efektivitas Pemberian Air Rebusan Bawang Putih Terhadap Tekanan Darah Pada Lansia Penderita Hipertensi - Imelda Erman; Desy Ramadhani; Indra Febriani; Ari Athiutama; Sumitro Adi Putra (Jurusan Keperawatan, Poltekkes Kemenkes Palembang, 2025)
Background: Old age is a phase of decline in intellectual and physical abilities, and experiencing structural and functional damage to the large arteries that carry blood away from the heart causes more severe hardening of the arteries and high blood pressure. Hypertension is a condition in which a person experiences an increase in blood pressure above normal which results in an increase in morbidity and mortality The purpose of this study was to determine the effectiveness of giving garlic boiled water on blood pressure in the elderly. Methods: This study uses a quasi-experimental research design with a non-equivalent control group design. The sampling technique in this study was non-porbality sampling with a purposive sampling approach. With a sample of 15 respondents in the intervention group and 15 respondents in the control group. Analysis of the data in this study used the Mann Withney U statistical test. Results: Based on the results of the analysis using the Mann Withney U parametric test, the average blood pressure before and after administration of garlic boiled water with p Value = 0.000 for systolic blood pressure and p Value = 0.002 for diastolic blood pressure., where the p value of systolic and diastolic blood pressure is smaller than the value of (0.05) which means that there is a significant effect between the administration of garlic boiled water and systolic and diastolic blood pressure. Conclusion: There is a significant difference in the average blood pressure before and after giving garlic boiled water. The results of this study can be input for the caretaker of the elderly social institution, our hope in overcoming high blood pressure in the elderly with hypertension.